Psychogenic Nonepileptic Seizures (PNES) classification: still “time for progress” - Luciano de Paola; W. Curt LaFrance (2021)
Some 20 years ago, in a galvanizing editorial written for the inaugural issue of Epilepsy and Behavior journal, John Gates, a pioneer on the field, proclaimed a “time for progress” on nonepileptic seizures. He acknowledged the tremendous progress made during the prior two decades in the field. Nonetheless, he recognized that “much work remained to be done”. Gates’ prophetic words, then, hold true, today. In fact, terminology and classification of nonepileptic seizures encompassed Gates’ initial concerns on that visionary editorial. [...]